Does footwork rule in netball increase chances of ACL injury in healthy competitive netball athletes? - Zhou, Regine Yongsi (Nanyang Technological University, 2021)
Background: Though mechanisms, risk factors and intervention programmes of non-contact ACL injury have been identified, elite netballers still find themselves highly susceptible to this injury. The footwork rule in netball that could potentially alter or restrict certain movements that may increase risk of non-contact ACL injury, is possibly understudied. Purpose: The purpose this study is to use kinematic analysis to determine if footwork rule in netball increases knee valgus and the risk of non-contact ACL injury in competitive netballers. Methods: A randomised crossover study design was adopted to obtain results from sixteen female competitive netball players aged 21-35 years old. Each participant performed two different one-foot landing conditions (legal and illegal) on their dominant leg. The data of knee valgus angles in participants was collected using a high-speed video camera at 240Hz and analysed using Kinovea software. Statistical analysis was done using descriptive statistics and one-way repeated measures ANOVA, to determine any differences in knee valgus angles between the different landing conditions. Results: 1 set of participant data was excluded from the study due to incomplete collection. Findings from fifteen competitive netballers showed no significant differences (P > .05) in knee valgus angles between the legal netball landing and illegal netball landing. The legal landing scenario generally displayed lower mean knee valgus angles than in the illegal landing scenario. Conclusions: The data clearly showed no significant advantage in allowing extra steps (illegal landing) to be taken during landing. The footwork rule in netball does not increase knee valgus and risk of ACL injury in competitive netballers.